Pengaruh Warna Pelapis dan Ketebalan Lapisan Pada Proses Zinc Electroplating Terhadap Laju Korosi Baja AISI 1015 (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
To improve the material's corrosion resistance, metal plating can be done. The main purpose of electroplating is to increase corrosion resistance and beautify the appearance with a variety of colors. The purpose of this study was to examine the effect of coating color variations on the corrosion rate of low carbon steel. The research method used was experimental. Using zinc electroplating and trivalent passivation treatment. Corrosion rate testing using the method weight loss, immersion period of 7 days with 3.5% NaCl corrosive medium. Layer thickness testing was carried out using the micro photo method. The research were obtained by directly observing the experimental results which were presented in tables and graphs. The results showed that there was an effect of coating color variations on the corrosion rate of AISI 1015 steel in the form of a decrease in the corrosion rate of each coating color variation. The lowest corrosion rate is in the black coating 0.016840030 mmpy. The layer thickness also affects the corrosion rate of AISI 1015 Steel. The higher the coating thickness in the process zinc electroplating , the lower the corrosion rate of AISI 1015 Steel.